Pengaruh pengungkapan sukarela, asimetri informasi, dan manajemen laba terhadap cost of equity capital pada perusahaan manufaktur - SOFIA PRIMA DEWI; JEFFRY SETIADY CHANDRA (Jurnal Bisnis dan Akuntansi, 2016)
The purpose of this study was to obtain empirical evidence about the influence of voluntary disclosure, information asymmetry, and earning management against cost of equity capital on manufacturing companies listed in the Indonesia Stock Exchange during the year 2012-2014. The samples used were 138 manufacturing companies. The results indicate that information asymmetry and earning management have an influence on cost of equity capital, while voluntary disclosure have no influence on cost of equity capital.